Taxpayer Compliance Analysis with Tax Knowledge, Tax Sanctions, and Income Levels Through Taxpayer Awareness as Moderating Variables - Tutik Dwi Karyanti; Zumrotun Nafiah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The Micro, Small and Medium Enterprises (MSME) sector is one of the drivers of the Indonesian economy because of its large number and growth. This sector is also considered by the Government as a tax supplier. SMEs are expected to have a high level of tax compliance. Tax knowledge, tax sanctions, income levels, and awareness of taxpayers are some of the factors that can affect the level of compliance of MSME taxpayers. Therefore, the purpose of this study was to analyze taxpayer compliance with tax knowledge, tax sanctions, and income levels through taxpayer awareness as a moderating variable. This study uses a correlative research design. This research was conducted on MSMEs in Semarang City which have a Taxpayer Identification Number (NPWP) with a total sample of 258 respondents. Collecting data using a questionnaire distributed with google form and data analysis techniques using path analysis with Partial Least Square (PLS) Structural Equation Modeling (SEM) with Smart PLS software version 3.3.5. The results showed that tax knowledge, tax sanctions, income levels, and taxpayer awareness had a positive and significant effect on taxpayer compliance. Taxpayer awareness becomes a moderating variable of the effect of tax sanctions on taxpayer compliance and is not a moderating variable of the effect of tax knowledge and income level on taxpayer compliance. The results of this study indicate that the better the tax sanctions with good taxpayer awareness, the taxpayer compliance will also increase.